2019
DOI: 10.22540/jfsf-04-065
|View full text |Cite
|
Sign up to set email alerts
|

Beyond balance and mobility, contributions of cognitive function to falls in older adults with cardiovascular disease

Abstract: Objectives: Older adults with cardiovascular disease (CVD) are at risk for cognitive impairment. Cognitive function is associated with falls in older adults however it is unknown if a relationship exists between cognitive function and falls in CVD. The aim of this study was to examine the contributions of cognitive function on falls in older adults with CVD. Methods: A secondary analysis was performed on data from the Health and Retirement Study cohort 2010 (N=3413) of older adults with CVD. Group assignment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…These differences were in depressive symptoms, physical performance, and FOF, and were consistent with previous studies 36,37. For example, a study demonstrated that fallers with CVD have slower gait speed, more balance impairment, and weaker grip strength than those with no falling history 38. Another found that depression and lower exercise capacity could predict overall functional decline among older adults with coronary heart disease 39.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These differences were in depressive symptoms, physical performance, and FOF, and were consistent with previous studies 36,37. For example, a study demonstrated that fallers with CVD have slower gait speed, more balance impairment, and weaker grip strength than those with no falling history 38. Another found that depression and lower exercise capacity could predict overall functional decline among older adults with coronary heart disease 39.…”
Section: Discussionsupporting
confidence: 86%
“…36,37 For example, a study demonstrated that fallers with CVD have slower gait speed, more balance impairment, and weaker grip strength than those with no falling history. 38 Another found that depression…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, little research has investigated the crucial intertwining of EF, measures of physical mobility (balance and fall risk), and cardiovascular disease (potential risk factors for CVD and VCI; [ 17 ]) [ 25 , 26 ] and no study has investigated this relationship in older people with CVD.…”
Section: Introductionmentioning
confidence: 99%